2020
DOI: 10.3389/fphar.2020.568477
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Camrelizumab and Its Combination With Apatinib in Various Solid Cancers

Abstract: Background: Camrelizumab (SHR1210) is a high-affinity, humanized immunoglobulin programmed cell death 1 (PD-1) monoclonal antibody. It was developed by Jiangsu Hengrui Medicine Co. Ltd. and has been approved for relapsed or refractory classical Hodgkin lymphoma patients and hepatocellular carcinoma patients in China. Apatinib is an orally administered vascular endothelial growth factor receptor-2 (VEGFR-2) tyrosine kinase inhibitor and has been approved for advanced gastric adenocarcinoma or gastroesophageal j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“… 13 , 15 , 25 , 27 , 34 , 37 The mechanism by which camrelizumab causes RCCEP is not fully understood. When combined with the antiangiogenic agent apatinib, the incidence was substantially lower (23.6%) compared with camrelizumab alone, in line with the findings in other studies of camrelizumab plus apatinib 22 , 28 , 29 or another antiangiogenic agent famitinib. 31 , 32 Our previous immunohistochemical analysis found strong capillary endothelial cell staining (CD31) in the dermis, as well as markedly high expressions of endothelial cell proliferation markers (Ki-67) and vascular endothelial growth factor-A (VEGF-A) in the lesion tissues, indicating activation of VEGFR2 signaling.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“… 13 , 15 , 25 , 27 , 34 , 37 The mechanism by which camrelizumab causes RCCEP is not fully understood. When combined with the antiangiogenic agent apatinib, the incidence was substantially lower (23.6%) compared with camrelizumab alone, in line with the findings in other studies of camrelizumab plus apatinib 22 , 28 , 29 or another antiangiogenic agent famitinib. 31 , 32 Our previous immunohistochemical analysis found strong capillary endothelial cell staining (CD31) in the dermis, as well as markedly high expressions of endothelial cell proliferation markers (Ki-67) and vascular endothelial growth factor-A (VEGF-A) in the lesion tissues, indicating activation of VEGFR2 signaling.…”
Section: Discussionsupporting
confidence: 88%
“…Previous reports from individual clinical trials mainly presented the incidence of RCCEP following treatment with camrelizumab alone or in combination. 6 , 13 16 , 18 40 There is a lack of systematic reporting on clinical characteristics of RCCEP, such as time to onset, duration, and remission data, especially in patients treated with a camrelizumab combination. Similarly, the correlation between RCCEP and efficacy was analyzed from individual clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that antiangiogenic agents may have the ability to improve immunosuppression. Currently, numerous clinical studies have demonstrated the promising antitumor effects of combining ICIs with antiangiogenic agents in various solid tumors, such as lung cancer, hepatocellular carcinoma, colon adenocarcinoma, gastric cancer, melanoma, renal cell carcinoma, and breast cancer ( 31 33 ).…”
Section: Discussionmentioning
confidence: 99%